The bro code : the fallout of raising boys to objectify and subordinate women - Keith, Thomas, 1958- (New York, NY : Routledge, 2021)
"Extending from the belief that masculinities are multiple, consisting of complexities and constructions that make up the traits associated with each, this book explores the various ways in which boys and men are conditioned to view women as inferior to themselves and predominantly sexual objects-and the deleterious effects this has on both women and men, society, and culture at large. Beginning in childhood, the book provides a critical framework to understand one form of masculinity referred to as "bro culture," and how it is reproduced and reinforced through popular culture, social institutions and patriarchal forms of religion and politics. Weaving together current research with illuminating historical and contemporary examples, Thomas Keith unpacks the attitudes, beliefs, and behaviors that constitute this subculture and reveals the ways in which traditional and outdated codes of manhood, power, and gender relations have evolved into problematic forms of sexism, misogyny, and abuse. For as much as popular culture is revealed to be a contributing factor in the passage of bro codes, the book also includes examples of cultural forces that are challenging and seeking to overthrow the core tenets in powerful and lasting ways. Timely and thought-provoking, The Bro Code addresses the implications of an enduring social problem and moves us to reflect on ways to empower men away from this toxic form of masculinity"--
Raising boys on sexism -- Bro culture in the age of #metoo -- Frat life: a continuum from honor societies to toxic bro-hood -- The bro code of silence: how men's silence harms women and men -- Advertising's sexist call to men -- A bro-manual to movies, tv, and games -- Musical misogynists: the beat of bro culture -- Pornography: sex-ed for bros -- Trump and the bro world of political sexism -- Religious bros.
OCLC-licensed vendor bibliographic record.
Keywords: Masculinity; Men -- Identity; Sex discrimination against women; Misogyny; SOCIAL SCIENCE / Men's Studies; SOCIAL SCIENCE / Sociology / General